Hubungan Asupan Lemak, Asupan Serat dan Aktivitas Fisik dengan Kadar Trigliserida pada Penderita Diabetes Melitus Tipe 2 di Puskesmas Grogol, Sukoharjo: Association between Fat Intake, Dietary Fiber Intake, Physical Activity with Triglyceride Levels among Type 2 Diabetes Mellitus Patients at Grogol Health Center, Sukoharjo - Safitri, Anisa Nur; Kusumawati, Dewi; Muhlishoh, Arwin; Avianty, Selma (Universitas Airlangga, 2024)
Background: Hyperlipidemia is closely associated with dietary intake and physical activity. Excessive dietary fat intake, inadequate dietary fiber, and low physical activity will increase the risk of obesity and lipid profile disorder among type 2 diabetics. Objectives: This study aimed to identify the association between fat intake, dietary fiber intake, and physical activity with triglyceride levels among type 2 diabetics. Methods: A cross-sectional study was conducted using Sequential Random Sampling on 31 patients with type 2 diabetes with dyslipidemia from Grogol Community Health Center, Sukoharjo, in March 2023. The 3x24-hour food recall nonconsecutive days was used to collect data on fat and fiber intake, the International Physical Activity Questionnaire-Short Form (IPAQ-SF) was employed to obtain physical activity data, and the patient's medical record for the last month was utilized to obtain fasting blood sugar and triglyceride levels. The statistical test was carried out using the Spearman Rank correlation test. Results: Around 54.8% of subjects had excessive fat intake (60.90 g/day); 96.8% of subjects had severe deficit fiber intake (9.74 g/day); 51.6% of subjects had low physical activity (894.74 METs/minute/week). A statistically significant association exists between fat intake and level of triglyceride (p=0.005; r=0.493), but there was no significant association between dietary fiber intake and triglyceride levels (p=0.897; r=0.024), and there was no significant association between physical activity and level of triglyceride (p=0.394; r=-0.159). Conclusions: There is a significant association between fat intake and the level of triglyceride. As such, it is necessary to decrease intakes of saturated fat and trans fatty acids; replacing them with unsaturated fatty acids could be beneficial in lowering triglyceride levels.